ANALISIS PARTISIPASI MASYARAKAT DALAM PEMANFAATAN RUANG TERBUKA HIJAU RANTAU BARU DI KOTA RANTAU PROVINSI KALIMANTAN SELATAN - Isma Sari; Taufik Hidayat; Danang Biyatmoko; Suyanto Suyanto (Jurnal Hutan Tropis, 2019)
The Tapin Regency Government seeks to provide public Green Open Space in Rantau City, the process of managing good and sustainable Green Open Space cannot be separated from several things, one of which is community participation in utilizing the presence of Green Open Space.Rantau City has a Rantau Baru Green Open Space that is always visited by residents every day because it is strategically located in the center of Rantau City and has attractive facilities, namely an artificial lake as a water bicycle playing arena. The purpose of this study was to analyze community participation in the utilization of the Rantau Baru Green Open Space and the efforts of the Tapin District Government in encouraging community participation in the management of green open space. This study uses a mixed research method that combines quantitative and qualitative approaches with data collection techniques through interviewing informants, direct observation to the field and distributing questionnaires to respondents, namely visitors to Rantau Baru Green Open Space and other secondary data collection in the form of written data from various libraries and photo documenting during research. The results showed that the community was very happy with the existence of the Rantau Baru Green Open Space but they had lack of participation in its utilization and management, it was concluded from the percentage of visitor answers contained in the questionnaire and also seen from the behavior of the community when visiting Rantau Baru Green Open Space. However, Local Government Agencies will continue to consistently improve the quality of facilities and infrastructure in Rantau Baru Green Open Space so that people are expected to be interested in visiting and feel comfortable doing recreational activities and light exercise in the Rantau Baru Green Open Space.